The question of national culture in multi-ethnic Malaysia / Qasim Ahmad - Ahmad, Qasim (Universiti Teknologi MARA, Shah Alam, 2005)
Present day Federation of Malaysia consists of eleven states in its Western part and two big ones in the Eastern. West Malaysia (approximately 132,000 square kilometres in size) is a peninsular jutting out from the south portion of Thailand with the Straits of Malacca to its West, the South China Sea to its east and the Singapore Island to its south. East Malaysia (200,000 square kilometres), occupying a significant part of the land mass of the island of Borneo, is separated from West Malaysia by an about 500 kilometre stretch of the South China Sea. Here Malaysia shares common land broders with Indonesia and Brunei while the Philippines lies not too far north from Sabah (one of the two Eastern states, the other being Sarawak) across the Sulu Sea.